Association between changes in urine output and successful indomethacin treatment for patent ductus arteriosus in preterm neonates. (24th November 2020) - Louis, Deepak; Dey, Arjun; Jain, Amish
Abstract : Aim: To investigate the relationship between changes in urine output during indomethacin treatment and ductal closure in preterm neonates. Methods: It is a retrospective study in neonates ≤32 weeks who had received two courses of indomethacin for PDA treatment over a 5‐year period. Indomethacin courses with pre‐ and post‐echocardiography confirmation of PDA status were included. Various urine output indices were collected and compared between successful versus unsuccessful indomethacin courses. Indomethacin treatment success was defined as: (i) where PDA closed or became haemodynamically insignificant (hisPDA) after treatment and (ii) only including neonates where PDA had complete closure after treatment. ROC analysis was performed to examine predictive ability of urine output during indomethacin for treatment success. Results: One hundred and eight indomethacin courses (first course: 52, second course: 56) in 80 neonates were included. The mean gestational age and birthweight were 25.4 ± 1.3 weeks and 762 ± 165 g, respectively. Irrespective of the definition used, there was no significant differences seen in any of urine output parameters between groups, except for a higher urine output during indomethacin associated with complete PDA closure (3.6 ± 1.3 vs. 3.0 ± 1.0 mL/kg/h, P = 0.02). The incidence of significant oliguria, hyponatraemia and need to withhold/delay indomethacin doses were also similar across groups. Conclusion: Urine output was not a useful predictor of ductal response to indomethacin treatment in preterm neonates.